2011
DOI: 10.1371/journal.pone.0018734
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Numbers of Blood Dendritic Cells and Defective Function of Regulatory T Cells in Antineutrophil Cytoplasmic Antibody-Associated Vasculitis

Abstract: BackgroundDendritic cells (DC) and regulatory cells (Treg) play pivotal roles in controlling both normal and autoimmune adaptive immune responses. DC are the main antigen-presenting cells to T cells, and they also control Treg functions. In this study, we examined the frequency and phenotype of DC subsets, and the frequency and function of Treg from patients with ANCA-associated vasculitis (AAV).Methodology/Principal FindingsBlood samples from 19 untreated patients with AAV during flares and before any immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 62 publications
5
55
0
Order By: Relevance
“…DCs were identified using 6-color flow cytometry assay as described previously [22], [23]. Briefly, whole blood samples were stained with the following antibodies: CD45-Amcyan, Lineage cocktail1-FITC, HLA-DR-APC-Cy7, CD11c-PECy7 and CD123-PECy5, all from BD Biosciences.…”
Section: Methodsmentioning
confidence: 99%
“…DCs were identified using 6-color flow cytometry assay as described previously [22], [23]. Briefly, whole blood samples were stained with the following antibodies: CD45-Amcyan, Lineage cocktail1-FITC, HLA-DR-APC-Cy7, CD11c-PECy7 and CD123-PECy5, all from BD Biosciences.…”
Section: Methodsmentioning
confidence: 99%
“…They also noted that that increased circulating CD4+ Foxp3+ cells was associated with more rapid disease remission [64]. The suppressive function of Tregs from ANCA disease patients was markedly decreased in ANCA disease patients with active disease but more normal during remission [65]. Free et al reported abnormalities in the suppressive Treg network as well as increased frequency of a distinct proinflammatory suppression-resistant effector CD4+ T cell population in patients with active ANCA disease [66].…”
Section: B Cell Regulation In Anca Diseasementioning
confidence: 99%
“…Impaired immune responses to BKV infection in KTX include decreased production of specific antibodies B cells, ineffective immune surveillance by T cells, and diminished dendritic cells [29]. Interestingly, AAV patients have been shown to have decreased dendritic cell numbers during active disease and in remission [30]. Despite this, we did not find any evidence of BKV replication in our immunosuppressed vasculitis patients.…”
Section: Discussionmentioning
confidence: 76%